Evaluation and Design of Affordable and Novel HIV-1 Drug Resistance Assays: - Wallis, Carole Lorraine (My University, 2006)
Approximately 5 million individuals are infected with HIV/AIDS in South Africa. The South African government has initiated a National Anti-retroviral therapy (ARV) Program to manage this disease. The emergence of drug resistance to ARV therapy is of great concern. Commercial gold standard sequence-based genotyping assays for monitoring resistance are unaffordable. This project aimed at developing affordable methods to detect specific point mutations relevant to HIV-1 subtype C. The Oligonucleotide Ligation assay (OLA), a real-time PCR assay and a Restriction Fragment Length Polymorphism (RFLP) assay were explored. Results were compared to the Viroseq genotyping assay. OLA performed poorly on HIV-1 subtype C samples and needs modification. The real-time PCR assay using short Minor Groove Binding probes, accurately detected the K65R mutation. The Mae III RFLP assay detected all V106M mutations accurately. Longitudinal cohort studies are required to confirm relevant mutations, appropriate assays and algorithms for resistance monitoring in HIV-1 subtype C.
Faculty of Health Sciences, Master of Science in Medicine, 9803855e
Keywords: HIV; PCR; ARV; South Africa; disease